Nauczyciel polonista wobec problemu uzależnień od mediów (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
Media addiction is one of the most serious behavioral addictions today. The aim of the article is to reflect on the role of Polish language teachers in the prevention of e-addictions. This text is pioneering. It presents specific methodological proposals that teachers can use in the educational process. They are based on the analysis and interpretation of various cultural texts (story, article, images), supplemented with selected content from the field of humanities and social sciences.